A carbide-reinforced Re0.5MoNbW(TaC)0.8 eutectic high-entropy composite with outstanding compressive properties. (15th July 2021) - Wei, Q.Q.; Xu, X.D.; Li, G.M.; Luo, G.Q.; Zhang, J.; Shen, Q.; Wu, C.L.
Abstract: Refractory high-entropy alloys are promising high-temperature materials owing to their excellent softening resistance. However, most RHEAs that can withstand softening at 1200 °C usually suffer from apparent brittleness at room temperature. Here, a high strength-ductile matching Re0.5 MoNbW(TaC)0.8 eutectic high-entropy composite (HEC) consisting of body-centered-cubic and multi-component carbide phases was fabricated by arc melting. The HEC exhibits a high yield strength (1340 MPa), ultimate compressive strength (2347 MPa) and plasticity (8.90 %), which exceeds those of previously reported RHEAs and HECs. Quantitative calculations based on experimental observations suggest that semi-coherent phase interface plays an essential role for strength enhancement, and interfacial dependent strengthening dominates among the interface strengthening terms. Our study envisages a strategy to design strong and ductile HECs aiming at high-temperature applications. Graphical abstract: Image, graphical abstract